2021
DOI: 10.21608/ejchem.2021.73925.3658
|View full text |Cite
|
Sign up to set email alerts
|

Cypermethrin-Induced Lung Damage in Albino Rats: The Preventive Impact of Moringa oleifera

Abstract: Cypermethrin (CYP) is a popular environmental toxicant because of its wide-ranging use as a broad-band insecticide. The purpose of this research was to explore the potential impact of Moringa oleifera leaves extract (MOLE) as a protective agent against cypermethrin-induced lung toxicity in male albino rats. Forty experimental animals were allocated into four groups. G1 served as the negative control, G2, G3 and G4 were orally treated with MOLE (250 mg/kg body weight), CYP (26.15mg/kg body weight) and CYP + MOL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
1
2
0
Order By: Relevance
“…It has been reported that cell membranes are peroxidized in lung tissue of rats administered pyrethroid 44 . In another study, it was stated that CYP causes lipid peroxidation in lung damage 45 . In our study, it was determined that the MDA level increased with CYP (25 mg/kg orally) administration in the lung tissue, and decreased depending on the dose in QUE administration.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…It has been reported that cell membranes are peroxidized in lung tissue of rats administered pyrethroid 44 . In another study, it was stated that CYP causes lipid peroxidation in lung damage 45 . In our study, it was determined that the MDA level increased with CYP (25 mg/kg orally) administration in the lung tissue, and decreased depending on the dose in QUE administration.…”
Section: Discussionsupporting
confidence: 48%
“…44 In another study, it was stated that CYP causes lipid peroxidation in lung damage. 45 In our study, it was F I G U R E 7 Effects of cypermethrin and quercetin administrations on ATF6, PERK, IRE1α, and GRP78 mRNA transcript levels in lung tissues of rats.…”
Section: Discussionmentioning
confidence: 69%
“…Meanwhile, other patient classes exhibit steroid resistance and persistence of asthma, which entails a high dose and long-term glucocorticoid treatment [ 25 ]. The current findings showed that cypermethrin, a widely used pesticide with common indoor and outdoor exposures [ 26 ], aggravated lung inflammation and was associated with dexamethasone irresponsiveness in the OVA-immunized rats. Notably, PFD treatment improved the histobiochemical pulmonary alterations and could replace dexamethasone treatment, bypassing steroid resistance.…”
Section: Discussionmentioning
confidence: 84%